Microstructures in Siderite - Khan, M. Riaz (Journal of Himalayan Earth Sciences, 1987)
Transmission Electron Microscopy (TEM) is a new technique in the study of internal structure of minerals. Siderite minerals from two localities are selected for investigation with TEM, coupled with EDX microanalysis and optical methods. The microstructures present are similar to those observed in other carbonates. The major microstructural features are the curving and branching ribbons in siderite regions and lath-like defects in calcitic grains present in Erzberg siderite. These laths are found dolomitic in structure. Similar microstructures have already been reported in saddle dolomites (Barber et al., 1985). Small calcite structured precipitates were encountered in the calcite grains, where iron concentration exceeds the already reported solubility limit. The occurrence of "c" type spots in the calcitic structure and their presence in more than one equivalent directions is also reported in this paper.